Hybrid Iterations for the Fixed Point Problem and Variational Inequalities. (27th August 2014) - Zhu, Li-Jun; Kang, Shin Min; Yao, Zhangsong; Kwun, Young Chel
Abstract : A hybrid iterative algorithm with Meir-Keeler contraction is presented for solving the fixed point problem of the pseudocontractive mappings and the variational inequalities. Strong convergence analysis is given as l i m n → ∞ d ( S T x n, T S x n ) .